2016
DOI: 10.9790/2402-1008011418
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Development of Fortified Pasta with Ginger Powder

Abstract: Abstract:Pasta is a popular food and its quality can also measured by appearance of flavour and texture.Present study was undertaken to evaluate the quality of pasta supplemented with different quantities of ginger powder. In the present study four samples (C, C1, C2, and C3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…Addition of carrot puree in formulation disturbs the gluten matrix which leads to the weakening of noodles structure. Similar results for decrease in firmness values were reported by Rekha et al () by addition of vegetable puree in pasta, Mishra and Bhatt () in fortified pasta with ginger powder. Krishnan and Prabhasankar () also reported decrease in firmness of noodles prepared by incorporation of green banana flour.…”
Section: Resultssupporting
confidence: 88%
“…Addition of carrot puree in formulation disturbs the gluten matrix which leads to the weakening of noodles structure. Similar results for decrease in firmness values were reported by Rekha et al () by addition of vegetable puree in pasta, Mishra and Bhatt () in fortified pasta with ginger powder. Krishnan and Prabhasankar () also reported decrease in firmness of noodles prepared by incorporation of green banana flour.…”
Section: Resultssupporting
confidence: 88%
“…Protein content of fish noodles observed in this study was similar to the findings of the dried noodles prepared from motan fish meal which revealed higher content of protein in noodles with lower moisture content [25]. Mishra and Bhatt [26] found 1.14% fat content in pasta. But, the fat content found in this study is higher than the reported value and this is might be due to the inclusion of 5 ml soybean oil and different amount of silver carp muscle in the noodles.…”
Section: Proximate Composition Of Prepared Noodlessupporting
confidence: 87%
“…Environmental biotechnology provides creative ways to manage medical waste sustainably, but there are many obstacles that must be overcome before it can be put into practice successfully [45]. b.…”
Section: Discussionmentioning
confidence: 99%